Application of physical therapy methods for patients after stroke with spasticity in the early period - Homola , Alona; Tsiganenko , Alexander (The Ukrainian Scientific Medical Youth Journal, 2023)
acute cerebrovascular accident is the leading cause of disability. Stroke ranks 4th among diseases that lead to death or disability. The consequences of stroke include neurological disorders, motor disorders (plegia, hemiparesis, paresis, muscle spasticity), loss of sensation, pelvic dysfunction, loss of coordination and balance, high risk of falls, and impaired ability to move independently and perform daily activities. To achieve optimal independence, stroke patients need qualified rehabilitation care as part of a multidisciplinary team. Evidence-based medicine, treatment, and rehabilitation interventions have improved significantly in the acute and early periods for stroke patients. However, in the late period, today, more than half of patients remain limited in their daily activities and have movement disorders that significantly affect their quality of life and independence. Description of the objective. To substantiate the use of evidence-based medicine methods in physical therapy to restore motor function in patients after stroke in the early period. Materials and methods. From October to December 2021, 20 patients with spasticity, aged 47-85 years, who had suffered an ischemic and hemorrhagic stroke, took part in the examination and rehabilitation activities at Kyiv City Clinical Hospital № 6, Palliative Care Department, for a period of 3 weeks to 1 month. Voluntary consent for examination, treatment, and rehabilitation was obtained from all patients and their caregivers. The diagnostic methods used were computed tomography, magnetic resonance imaging, and, if necessary, laboratory tests. Tests and scales for physical therapy were used to determine functional impairment in stroke patients with muscle spasticity: Rankin Scale, Riverbed Mobility Index, Pain Score, Modified Ashworth Scale, Degree of Arm and Hand Recovery; Degree of Leg and Foot Recovery. Results. After analyzing the methods of evidence-based medicine on the topic of the problem, we have confirmation that in the early period, recovery rates are high. However, in the late period after a stroke, the onset of muscle spasticity significantly limits the motor capabilities of patients and complicates the recovery process. In the late period, the effectiveness of methods to overcome spasticity has not been fully developed, and attention is not focused on the complications that arise and accompany them throughout the recovery period. The appearance of muscle spasticity significantly limits the motor capabilities of patients, affects the psycho-emotional state of a person, and causes pain, which prevents the full use of the affected limb. Muscle spasticity inhibits and complicates the restoration of motor function in the long term. Conclusions. The study confirms the high effectiveness of the proposed methods of evidence-based medicine in reducing pain and increasing the range of motion in the shoulder, elbow, and wrist joints in the early period in patients after stroke. As for the late period, this issue remains incomplete and requires further study. In the palliative care unit of Kyiv City Clinical Hospital № 6, an individual multidisciplinary approach to patients after stroke was used, which contributed to the achievement of the goals. It can be stated that evidence-based medicine methods for the acute and early period have a positive effect on patient independence, and improve cognitive function and motor activity of the affected limbs.